Dancing standing still: healing the world from a place of prayer : a new edition of A lever and a place to stand - Rohr, Richard (Paulist Press, 2014)
Offers a critique of religion as a system that often creates an alternative pious world without really challenging oppression, materialism, and sectarianism in our modern world. Religion, he says, without this contemplative stance is often part of the problem. Drawing from Jesus parable of the rich man, Rohr believes that religion can only rediscover itself as a transformational system if it passes through the eye of a needle, if it overcomes its own temptation to power, wealth, and fundamentalism. A true contemplative stance crosses boundaries, is not concerned with who's in and who's out. --Amazon.com